How HDL protects LDL against atherogenic modification: paraoxonase 1 and other dramatis personae. Issue 4 (August 2015) - Soran, Handrean; Schofield, Jonathan D.; Liu, Yifen; Durrington, Paul N.
Abstract : Purpose of review: To summarize the current evidence about how HDL impedes the oxidative and glycative atherogenic modification of LDL. Recent findings: Paraoxonase 1 (PON1) is located on HDL. Meta-analysis of clinical epidemiological investigations reveals a substantial association of low serum PON1 activity with coronary heart disease incidence independent of other risk factors including HDL cholesterol and apolipoprotein AI (apoAI). Transgenic animal models also indicate an antiatherosclerotic role for PON1. However, highly purified and recombinant PON1 do not retain their antioxidant properties. Summary: The therapeutic potential of PON1 should be recognized in preventing atherosclerosis and combating infection and organophosphate toxicity. In unleashing this potential, it is important to consider that both highly purified and recombinant PON1 are dissociated from the lipid phase and other components of HDL, such as apoAI and apoM, all of which may be required for HDL (through its PON1 component) to hydrolyze more lipophilic substrates.